Comparative effectiveness of antiretroviral drug classes for the treatment of HIV infection in patients with high viral loads: a multicentre retrospective cohort study. Issue 1 (23rd September 2020) - Adams, JL; Murray, M; Patel, N; Sawkin, MT; Boardman, RC; Pham, C; Kaur, H; Patel, D; Yager, JL; Pontiggia, L; Baxter, J
Abstract : Objectives: We aimed to compare the effectiveness of antiretroviral therapy (ART) classes for achieving HIV RNA suppression to < 50 HIV‐1 RNA copies/mL within 6 months of initiation with high viral loads (VLs). Secondary objectives were to compare viral suppression (VS) at 12 weeks and 12 months, partial HIV RNA suppression to < 200 copies/mL, time to VS, time to rebound, and change in CD4 cell count. Methods: This was a multicentre, retrospective, observational study. Adult patients were included if they initiated ART between January 2005 and December 2016 with a VL ≥ 100 000 copies/mL. Results: There were 220 patients included in the study. The median VL was 252 919 [interquartile range (IQR) 149 472–500 000] copies/mL. Nonnucleoside reverse transcriptase inhibitor (NNRTI) recipients were more likely to achieve VS by 6 months compared to those initiating ART containing protease inhibitors (PIs) [75.4% vs . 44.1%, respectively; odds ratio (OR) 3.34; 95% confidence interval (CI) 1.62–6.90] or integrase strand transfer inhibitors (INSTIs) (75.4% vs . 55.8%, respectively; OR 2.40; 95% CI 1.03–5.58). VS at 12 weeks was more frequent with INSTI‐containing regimens than with PIs (28.9% vs . 9.0%, respectively; OR 4.10; 95% CI 1.69–9.92). VS at 12 months did not significantly differ between treatment regimens. Median time to complete VS for INSTI, PI and NNRTI recipients was 22.3 (95% CI 13.4–33), 30.1 (95% CI 25–36) and 19.9 (95% CI 16–22.3) weeks, respectively. There were no significant differences in time to viral rebound or change in CD4 cell counts. Conclusions: Patients with high VLs initiated on NNRTIs were more likely to achieve VS by 6 months on ART compared to INSTI and PI recipients.